Distal nail embedding treatment using autogenous nails. Issue 6 (25th October 2021) - Kashiyama, Kazuya; Nakano, Motoi; Higashi, Akihito; Ashizuka, Shoko; Moriuchi, Yuki; Iwao, Atsuhiko; Tanaka, Katsumi
Abstract: A regrowing nail tip after nail avulsion may excessively curve and invaginate into the nail bed. This is treated as a type of ingrown toenail, and is known as distal nail embedding. In most cases, further growth restores the original shape evenly over the nail bed. However, it is often painful and such cases may require treatment. We report a surgical approach that we applied to six cases of distal nail embedding involving pain or deformity of nails caused by a nail tip invaginating into the nail bed and/or cessation of forward nail growth. As our method involves removing a portion of the embedded tip edge nail and inserting the removed nail into the remaining depressed portion, the nail can grow over the bulge. In all six patients in whom we applied this method, the pain and nail deformity resolved and there was no recurrence. We used autogenous nails, which can reduce the pressure imbalance on a nail bed, and this contributed to improving the morphology of nails and nail beds. In addition, the risk of a hypertrophied nail is reduced because half of the nail adheres to the nail bed. Special materials are unnecessary and this method can be conducted with simple outpatient department procedures. There were no cases of a fixed nail section detaching due to a bulge at the nail tip. The inserted nail was maintained in all cases for several months until the nail grew over the bulge.